Assessing Public Transport Convenience for Achieving SDG 11.2 in Tangerang Municipality - Iqbal, Luthfi Muhamad; Taufani, Aditya Riski; Nababan, Martua Yan Steward; Kusumawardhani, Nadia Paramitha; Agnevia, Renita (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
A reliable urban transport system is essential for achieving sustainable cities and communities. The United Nations' Sustainable Development Goal (SDG) 11.2 targets universal access to safe, affordable, accessible, and sustainable transport systems by 2030. This study evaluates SDG 11.2 performance in Tangerang Municipality, examining progress toward this target. Using spatial analysis methods—such as buffer analysis, network and isochrone analysis, and spatial autocorrelation in GIS—this research assesses transit quality and accessibility. Data were collected through purposive sampling, analyzed using an online field survey, and assessed via a Likert scale. The findings reveal that only 13.85% to 22.47% of Tangerang’s population has convenient access to public transport, with coverage limited to 17.56% of the city’s area. A dispersed yet positive spatial autocorrelation exists between public transport patterns and population density, with a Moran's I value of 0.076. However, 36 out of 104 subdistricts remain underserved. Pedestrian convenience scored the lowest due to inadequate pedestrian infrastructure and sidewalk encroachment by street vendors. If no action is taken to address these issues, accessibility could decline from 22.4% to 16.51% by 2032, assuming a 2.6% annual population growth rate. Achieving an 85% public transport share by 2032 would require an annual improvement rate of 5.6% from 2020 onward. The study recommends an integrated public transport service expansion, enhanced transit quality, improved transport data collection, and public awareness campaigns to accelerate SDG 11.2 progress in Tangerang.